A Analisis Sistem Pentanahan Gedung Pascasarjana Menggunakan Metoda Tiga Titik Di Universitas Lancang Kuning: Analisis Sistem Pentanahan - Abrar Tanjung; Arlenny (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
The grounding system is a way to channel the electric current that occurs due to a lightning strike on an object in the building there is an electrical system used for electrical and electronic equipment. The grounding system is used to secure buildings from fire hazards due to lightning strikes, secure electrical and electronic equipment and humans connected by wires or conducting cables to electrodes that are installed in the ground. The research method analyzes data from the data obtained to obtain large values ​​of grounding resistance, short fault current, healthy phase increase and touch voltage and step voltage in the Unilak Postgraduate building. The purpose of this study is to analyze the value of the resistance of the grounding system, analyze the short-circuit fault current that occurs in the grounding system, analyze the phase voltage increase, and analyze the touch voltage and step voltage in the Lancang Kuning University Postgraduate building. By using the three-point research method, the calculation results on the grounding of the Postgraduate Building are 28 ohms, the neutral point resistance value is 0.00465 ohms, the touch voltage is 149.5 volts, the step voltage is 208 volts, the short circuit fault current calculation is 1, 15 amperes, while the healthy phase voltage increase is 308 volts.